Laminated body having excellent chemical resistance and transfer film for producing the laminated body
By providing a functional layer with a specific composition on the release layer of the transfer film, the problem of appearance deterioration of the laminated body in the chemical resistance test in the prior art is solved, and higher chemical resistance and less foil burrs are achieved.
Patent Information
- Application Number
- CN202280094928.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-22
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2042-09-22
AI Technical Summary
In the prior art, the laminate obtained by using a transfer film of a polyol compound and an isocyanurate modified isocyanate compound has problems of test agent penetration, expansion and cracking in the chemical resistance test, resulting in deterioration of appearance.
A functional layer containing a thermosetting resin of a specific composition is provided on the release layer of the transfer film. The thickness of the functional layer is 3 μm or more and 8 μm or less, and includes a polyol compound and a polyisocyanate compound. The hydroxyl value of the polyol compound is 20 mg KOH/g or more and 60 mg KOH/g or less, and the ratio of isocyanate groups to hydroxyl groups in the isocyanate compound is 0.5 or more and 3.0 or less.
Through this technical means, the obtained laminated body rarely deteriorates after chemical resistance test, and foil burrs are not easily generated during transfer processing, which significantly improves the chemical resistance of the laminated body.
Smart Images

Figure CN119053457B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a laminate having excellent chemical resistance and a transfer film capable of obtaining the laminate. Background Art
[0002] The following method has been widely used: a transfer film having a release layer, a functional layer (a protective layer, a coloring layer, a printing layer, a hard coating layer, an anti-reflection layer, a metal film layer, etc.) and an adhesive layer sequentially formed on a plastic film is used; the functional layer and the adhesive layer (hereinafter these layers are collectively referred to as the transfer layer) formed on the release layer of the transfer film are transferred from the release layer of the transfer film to the surface of the transfer object, thereby forming a transfer layer on the surface of the transfer object, and obtaining a laminated body endowed with various functions such as metallic gloss, design properties such as patterns, hard coating properties, anti-reflection properties, etc.
[0003] Furthermore, the laminate is used as various products such as home electrical appliances, automobile parts, sundries, paper containers, and labels.
[0004] When a laminate is used for automobile interior and exterior decoration, chemical resistance is generally required, for example, the following performance: even if a test agent such as sunscreen cosmetics and gasoline is applied to the surface of the laminate and left to stand at a high temperature of 80°C for 10 minutes, the appearance will not be defective. In addition, automobile manufacturers set their own specifications for chemical resistance, and excellent chemical resistance that can correspond to any of these specifications is even more highly expected.
[0005] Patent Document 1 discloses a transfer sheet (transfer film) having less foil burrs (a phenomenon in which all or part of the transfer layer in the non-transfer portion near the transfer portion is peeled off from the base sheet while being connected to the transfer layer). The transfer sheet is characterized in that: a release layer, a protective layer, a design layer (decorative layer), and an adhesive layer are sequentially formed on a base sheet (plastic film), and the protective layer contains a polyol compound and an isocyanurate-modified isocyanate compound. The transfer sheet is intended to reduce the generation of foil burrs.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2003-154794 Summary of the invention
[0009] Problems to be solved by the invention
[0010] When a laminate is obtained using the transfer film described in Patent Document 1, since the protective layer contains the usual polyol compound and isocyanurate-modified isocyanate compound, less foil burrs are generated during the transfer process, and the laminate can be obtained relatively cheaply. However, the laminate obtained using the transfer film described in Patent Document 1 has the following problems: since the protective layer contains the usual polyol compound and isocyanurate-modified isocyanate compound, it cannot become a tough layer. Although certain surface properties such as scratch resistance can be obtained, when the laminate is subjected to a chemical resistance test, the test agent penetrates from the surface of the transfer layer, causing expansion and cracking in the entire transfer layer and the substrate, and deteriorating the appearance. In particular, this problem is significant when the test agent uses sunscreen cosmetics and gasoline. Therefore, the subject of the present invention is to provide a laminate that solves all the above problems and a transfer film suitable for its manufacture.
[0011] Means for solving problems
[0012] As a result of intensive research, the inventors found that by providing a functional layer containing a thermosetting resin of a specific composition on the release layer of the transfer film (transfer layer side), it is possible to improve chemical resistance while suppressing the generation of foil burrs, thereby completing the present invention. That is, the transfer film and laminate of the present invention that solve the above-mentioned problems have the following configurations.
[0013] [Item 1]
[0014] A transfer film having at least a functional layer and an adhesive layer formed in sequence on a plastic film, wherein at least the thickness of the functional layer satisfying the following conditions a, b and c is 3 μm or more and 8 μm or less,
[0015] a) contains at least a polyol compound and a polyisocyanate compound,
[0016] b) the hydroxyl value of the polyol compound is 20 mgKOH / g or more and 60 mgKOH / g or less,
[0017] c) The ratio of the total number of isocyanate groups contained in the polyisocyanate compound to the total number of hydroxyl groups contained in the polyol compound ([NCO] / [OH] ratio) is 0.5 or more and 3.0 or less.
[0018] [Item 2]
[0019] The transfer film according to Item 1, wherein the functional layer includes at least a protective layer and an intermediate layer.
[0020] [Item 3]
[0021] The transfer film according to Item 1, wherein the functional layer comprises at least a protective layer, an intermediate layer, and a decorative layer.
[0022] [Item 4]
[0023] The transfer film according to item 3, wherein the decorative layer comprises at least one layer selected from the group consisting of a metal base layer, a metal thin film layer, a coloring layer, and a printing layer.
[0024] [Item 5]
[0025] The transfer film according to Item 4, wherein the decoration layer comprises a metal base layer and a metal thin film layer.
[0026] [Item 6]
[0027] A laminated body characterized by being obtained by transferring the transfer film described in Items 1 to 5 onto a substrate.
[0028] [Item 7]
[0029] A laminated body having at least an adhesive layer and a functional layer formed in sequence on a substrate, wherein at least the thickness of the functional layer satisfying the following conditions a, b and c is 3 μm or more and 8 μm or less,
[0030] a) contains at least a polyol compound and a polyisocyanate compound,
[0031] b) the hydroxyl value of the polyol compound is 20 mgKOH / g or more and 60 mgKOH / g or less,
[0032] c) The ratio of the total number of isocyanate groups contained in the polyisocyanate compound to the total number of hydroxyl groups contained in the polyol compound ([NCO] / [OH] ratio) is 0.5 or more and 3.0 or less.
[0033] [Item 8]
[0034] The laminate according to Item 7, wherein the functional layer includes at least a protective layer and an intermediate layer.
[0035] [Item 9]
[0036] The laminate according to Item 7, wherein the functional layer includes at least a protective layer, an intermediate layer, and a decorative layer.
[0037] [Item 10]
[0038] The laminate according to item 9, wherein the decorative layer includes at least one layer selected from the group consisting of a metal base layer, a metal thin film layer, a colored layer, and a printed layer.
[0039] [Item 11]
[0040] The laminated body according to Item 10, wherein the decorative layer comprises a metal base layer and a metal thin film layer.
[0041] Effects of the Invention
[0042] The laminate of the present invention is characterized in that the thickness of the functional layer satisfying the following conditions a, b, and c is 3 μm or more and 8 μm or less.
[0043] a) contains at least a polyol compound and a polyisocyanate compound,
[0044] b) the hydroxyl value of the polyol compound is 20 mgKOH / g or more and 60 mgKOH / g or less,
[0045] c) The ratio of the total number of isocyanate groups contained in the polyisocyanate compound to the total number of hydroxyl groups contained in the polyol compound ([NCO] / [OH] ratio) is 0.5 or more and 3.0 or less.
[0046] By making the functional layer have the above composition, it is possible to obtain a transfer layer that is not easily permeable to various components used in the chemical resistance test. As a result, the laminate of the present invention has less appearance deterioration caused by damage such as swelling and cracking on the entire transfer layer and the substrate after the chemical resistance test.
[0047] Since the transfer film of the present invention has a functional layer having the above composition, the laminate of the present invention obtained by using the transfer film of the present invention is less likely to suffer from appearance deterioration due to damage such as swelling and significant cracking after a chemical resistance test. In addition, the boundary between the transfer portion and the non-transfer portion in the functional layer of the present invention is easily broken, and foil burrs are less likely to occur during transfer processing.
[0048] Therefore, the transfer film of the present invention is the most suitable transfer film for producing the laminated body of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 This is a schematic diagram of a cross-sectional structure of one embodiment of the transfer film of the present invention in which a release layer, a protective layer, an intermediate layer, a metal base layer, a metal thin film layer, and an adhesive layer are sequentially formed on a plastic film.
[0050] Figure 2 This is a schematic diagram of a cross-sectional structure of one embodiment of the laminate of the present invention in which an adhesive layer, a metal thin film layer, a metal base layer, an intermediate layer, and a protective layer are sequentially formed on a substrate.
[0051] Figure 3 This is a schematic diagram of a cross-sectional structure of one embodiment of the transfer film of the present invention in which a release layer, a protective layer, an intermediate layer, and an adhesive layer are sequentially formed on a plastic film.
[0052] Figure 4 This is a schematic diagram of a cross-sectional structure of one embodiment of the laminate of the present invention in which an adhesive layer, an intermediate layer, and a protective layer are sequentially formed on a substrate. DETAILED DESCRIPTION
[0053] The transfer film of the present invention will be described below.
[0054] (Plastic film)
[0055] The plastic film used for the transfer film of the present invention is not particularly limited as long as it is a plastic film generally used for transfer films, and various conventionally known plastic films such as polyethylene terephthalate film, polycarbonate film, polyethylene film, polypropylene film, and polyamide film can be used.
[0056] The plastic film may be unstretched, uniaxially stretched, or biaxially stretched, and may contain various additives such as an antistatic agent, a colorant, a heat stabilizer, etc. The type of the plastic film may be appropriately selected depending on the desired use and purpose.
[0057] Furthermore, in order to make the transfer film of the present invention more designable, the surface of the plastic film (the surface on which the release layer is formed) may be subjected to uneven processing such as fine line processing, matte processing, embossing processing, etc.
[0058] The thickness of the plastic film used for the transfer film of the present invention is not particularly limited, but is preferably 12 to 250 μm. If the thickness of the plastic film is thinner than 12 μm, when a release layer is formed on the plastic film, or when the transfer film of the present invention is handled, it is not preferred that the film is not only easy to curl, but also easy to wrinkle and difficult to handle. If the thickness of the plastic film is thicker than 250 μm, the so-called stiffness will be increased, and when the transfer film of the present invention is used for transfer processing, it will be difficult to place it on the surface of the substrate as the transferred object, and it will be difficult to handle, so it is not preferred.
[0059] (Release layer)
[0060] A release layer may be formed in the transfer film of the present invention. If the protective layer described later satisfies the release property, a release layer may not be formed. The release layer is a layer formed on the plastic film for the following purpose: when the transfer film of the present invention is used for transfer processing, the transfer layer is easily peeled off from the release layer of the transfer film of the present invention. In addition, the release layer is not transferred or formed on the surface of the transfer object during the transfer processing, but is removed from the transfer object together with the plastic film.
[0061] The release layer is a layer containing resin. The resin used for the release layer is not particularly limited as long as it can achieve the above-mentioned purpose. Existing well-known resins such as polyethylene resin, polypropylene resin, polystyrene resin, vinyl chloride resin, polyester resin, acrylic resin, urethane resin, melamine resin, epoxy resin, etc. can be used. Any one of them or a mixed resin of two or more can be appropriately selected according to the purpose.
[0062] The thickness of the release layer may be appropriately selected within a range that can achieve the above-mentioned purpose, and is preferably in the range of 0.5 to 5 μm.
[0063] The release layer may be formed by any conventional coating method such as gravure coating, reverse coating, die coating, reverse gravure coating, or bar coating, and may be appropriately selected depending on the intended purpose.
[0064] (Functional layer)
[0065] The functional layer of the present invention is formed so that the thickness of the layer satisfying the following conditions is 3 μm or more and 8 μm or less.
[0066] a) contains at least a polyol compound and a polyisocyanate compound,
[0067] b) the hydroxyl value of the polyol compound is 20 mgKOH / g or more and 60 mgKOH / g or less,
[0068] c) The ratio of the total number of isocyanate groups contained in the polyisocyanate compound to the total number of hydroxyl groups contained in the polyol compound ([NCO] / [OH] ratio) is 0.5 or more and 3.0 or less.
[0069] There are no particular restrictions on the polyol compound, and for example, acrylic polyols, polyester polyols, polyether polyols, hydroxyl-containing fluorine resins, etc. can be used alone or in any combination thereof. In particular, acrylic polyol compounds are most preferably used from the viewpoint of imparting weather resistance in addition to chemical resistance.
[0070] As the isocyanate compound, there is no particular limitation, and for example, aromatic diisocyanate compounds such as toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), and xylylene diisocyanate (XDI), aliphatic diisocyanate compounds such as hexamethylene diisocyanate (HDI), isophorone diisocyanate (IPDI), hydrogenated diphenylmethane diisocyanate (hydrogenated MDI), and alicyclic diisocyanate compounds such as hydrogenated xylylene diisocyanate (hydrogenated XDI) can be used alone or in any combination. The resin satisfying the above conditions is represented as a resin that is a feature of the present invention in the following specification.
[0071] In addition, the functional layer may also contain a layer that does not meet the above conditions, and as its material, polyethylene resin, polypropylene resin, polystyrene resin, vinyl chloride resin, polyester resin, acrylic resin, urethane resin, melamine resin, epoxy resin and other existing known resins can be used, and any one or a mixed resin of two or more thereof can be appropriately selected according to the purpose of forming the layer. Furthermore, a curing agent such as an isocyanate compound may also be contained.
[0072] The hydroxyl value of the polyol compound in the resin that is a feature of the present invention is preferably 20 mgKOH / g or more and 60 mgKOH / g or less. If it is less than 20 mgKOH / g, sufficient crosslinking density cannot be obtained, and chemical resistance will deteriorate. In addition, if it is greater than 60 mgKOH / g, foil burrs are likely to occur. In addition, the ratio of the total number of isocyanate groups contained in the polyisocyanate to the total number of hydroxyl groups contained in the polyol ([NCO] / [OH] ratio) is preferably 0.5 or more and 3.0 or less. If it is less than 0.5, sufficient crosslinking density cannot be obtained, and chemical resistance will deteriorate. In addition, even if it is greater than 3.0, chemical resistance may sometimes deteriorate. In addition, the total thickness of the layer containing the resin that is a feature of the present invention in the functional layer is preferably 3 μm or more and 8 μm or less. When it is thinner than 3 μm, it is easy to be penetrated by the test agent in the chemical resistance test, which easily causes appearance degradation. In addition, if it is thicker than 8 μm, foil burrs are likely to occur during transfer processing.
[0073] As the configuration of the functional layer of the present invention, for example, the following combinations can be mentioned.
[0074] (Release layer) / Protective layer / Intermediate layer / (Adhesive layer),
[0075] (Release layer) / Protective layer / Coloring layer / (Adhesive layer),
[0076] (Release layer) / Protective layer / Intermediate layer / Coloring layer / (Adhesive layer),
[0077] (Mold release layer) / protective layer / intermediate layer / metal base layer / metal film layer / (adhesive layer),
[0078] (Release layer) / Protective layer / Intermediate layer / Coloring layer / Metal base layer / Metal film layer / (Adhesive layer)
[0079] In the above-mentioned examples, the layers shown in brackets represent layers located above and below the thickness direction of the illustrated functional layer. Of course, even in combinations other than these, any layer can be used according to the desired purpose. Any combination of these layers can contain a resin that is a feature of the present invention. For example, it can be a combination in which the protective layer and the intermediate layer are layers containing a resin that is a feature of the present invention, and the other layers contain a resin that is not a feature of the present invention, or the coloring layer and the metal base layer are layers containing a specific resin that is a feature of the present invention, and the other layers contain a resin that is not a feature of the present invention. Even if it is an arbitrary combination, as long as the total value of the thickness of the layer containing the resin that is a feature of the present invention is above 3μm, chemical resistance can be obtained.
[0080] (Protective layer)
[0081] The protective layer of the present invention is formed on the plastic film or release layer on the transfer layer side for the purpose of stabilizing the release properties of the transfer film of the present invention. During transfer, the plastic film or release layer and the protective layer are peeled off at the interface. As a result, the transfer layer of the obtained laminate is protected after being transferred and formed on the surface of the transferred object.
[0082] The resin described in the functional layer can be used in the protective layer. Furthermore, the protective layer can be added with one or more antistatic agents, ultraviolet absorbers, heat stabilizers, curing agents and other additives as needed, and the amount of each additive added can be appropriately selected according to the purpose. When the resin that is a feature of the present invention is used as the protective layer, from the viewpoint of peelability, it is preferred to provide the release layer. In the case where the release layer is not provided or the release property is unstable when only the release layer is provided, from the viewpoint of peelability, there is a case where the resin that is a feature of the present invention cannot be used. In this case, a resin that is not a resin that is a feature of the present invention but has good release properties can be used. Resins with good release properties may have poor chemical resistance, but in this case, by making the thickness of the protective layer less than 1 μm and using the resin that is a feature of the present invention in the intermediate layer described later, the appearance degradation can be suppressed to a degree that does not affect actual use.
[0083] The thickness of the protective layer may be appropriately selected within a range that can achieve the above-mentioned purpose, and is preferably in the range of 0.5 to 5 μm.
[0084] As a method for forming the protective layer, a conventionally known coating method such as gravure coating, reverse coating, die coating, reverse gravure coating, and bar coating can be used, and any method may be appropriately selected depending on the purpose.
[0085] (Middle layer)
[0086] The intermediate layer of the transfer film of the present invention is a layer formed on the protective layer for the following purpose: to supplement the chemical resistance of the functional layer other than the intermediate layer. That is, when the functional layer other than the intermediate layer contains the resin that is a characteristic of the present invention and has chemical resistance, there is no need to form an intermediate layer. In addition, when the thickness of the layer containing the resin that is a characteristic of the present invention in the functional layer other than the intermediate layer is insufficient, an intermediate layer containing the resin that is a characteristic of the present invention can be provided to obtain chemical resistance. When the above-mentioned or the following protective layer, metal base layer, coloring layer or printing layer cannot use the resin that is a characteristic of the present invention according to its purpose, in order to make the thickness of the layer containing the resin that is a characteristic of the present invention above 3μm, it is preferred to form an intermediate layer.
[0087] The intermediate layer can use the resin that is a feature of the present invention and has been described in the functional layer.
[0088] Furthermore, the intermediate layer may contain one or more kinds of additives such as an antistatic agent, an ultraviolet absorber, a heat stabilizer, and a curing agent as required, and the amount of each additive added may be appropriately selected depending on the purpose.
[0089] The thickness of the intermediate layer may be appropriately selected within a range that can achieve the above-mentioned purpose, and is preferably in the range of 0.5 to 5 μm.
[0090] As a method for forming the intermediate layer, a conventionally known coating method such as gravure coating, reverse coating, die coating, reverse gravure coating, and bar coating can be used, and any method may be appropriately selected depending on the purpose.
[0091] (Decorative layer)
[0092] The transfer film of the present invention may be formed with a colored layer using a colorant, a printed layer, and a metal thin film layer, which are formed for the purpose of imparting design to the transferred object.
[0093] (Coloring layer and printing layer)
[0094] The coloring layer is a layer formed on the entire surface or a part of the desired position of the transfer film of the present invention by adding a pigment or dye to the resin. The printing layer is a layer in which the colored portion is formed into a desired pattern. The resins described in the functional layer can be used in the coloring layer and the printing layer. The resins that are the characteristics of the present invention can also be used in the coloring layer and the printing layer. In addition, in the case where the resins that are the characteristics of the present invention cannot be used in the coloring layer and the printing layer, it is preferred to provide an intermediate layer containing the resins that are the characteristics of the present invention. Furthermore, various additives such as one or more antistatic agents, ultraviolet absorbers, heat stabilizers, curing agents, etc. can also be added as needed, and the amount of each additive added can be appropriately selected according to the purpose.
[0095] The thickness of the coloring layer and the printing layer can be a thickness that can obtain the desired effect of the coloring layer and the printing layer, and is preferably in the range of 0.5 to 5 μm, respectively, and can be appropriately selected according to the purpose of forming the coloring layer and the printing layer. In addition, the method for forming the coloring layer and the printing layer can use a known coating method such as gravure coating, reverse coating, die coating, reverse gravure coating, rod coating, screen printing, offset printing, etc., and can be appropriately selected according to the purpose.
[0096] (Metal base layer)
[0097] The metal base layer is formed for the purpose of making the protective layer, intermediate layer, colored layer or printed layer closely adhere to the metal thin film layer when the metal thin film layer described later is formed on the transfer film of the present invention.
[0098] The resin described in the functional layer can be used for the metal base layer.
[0099] In addition, when the resin having the characteristics of the present invention is used in the metal base layer, by using a resin having a ratio of the total number of isocyanate groups contained in the polyisocyanate compound to the total number of hydroxyl groups contained in the polyol compound ([NCO] / [OH] ratio) of 1.0 or more as the metal base layer, the close contact between the metal film layer and the metal film layer is enhanced, which is more preferred. In addition, when the resin having the characteristics of the present invention cannot be used in the metal base layer, it is preferred to provide an intermediate layer containing the resin having the characteristics of the present invention. Various additives such as one or more antistatic agents, ultraviolet absorbers, heat stabilizers, curing agents, etc. can be added as needed, and the amount of each additive added can be appropriately selected according to the purpose.
[0100] The thickness of the metal base layer may be appropriately selected within a range that can achieve the above-mentioned purpose, and is preferably in the range of 0.5 to 2 μm.
[0101] The metal base layer can be formed by any conventionally known coating method such as gravure coating, reverse coating, die coating, reverse gravure coating, or bar coating, and may be appropriately selected depending on the intended purpose.
[0102] (Metallic thin film layer)
[0103] The metal thin film layer is a layer formed mainly for the purpose of imparting metallic luster to the transferred object, and is a layer that is transferred together with the adhesive layer and formed on the surface of the transferred object during the transfer process. Furthermore, by using a metal compound described later in the metal thin film layer, it is also possible to impart properties such as barrier properties and conductivity in addition to the metallic luster, or to impart properties such as barrier properties and conductivity in place of the metallic luster.
[0104] The metal used in the metal thin film layer can be various known metals such as aluminum, chromium, tin, gold, silver, copper, zinc, silicon, nickel, indium, etc., or metal compounds such as oxides, sulfides, nitrides, etc. of the known metals, and can be appropriately selected according to the desired purpose.
[0105] Furthermore, the metal thin film layer may be a single layer or a plurality of layers of two or more. When the metal thin film layer is a plurality of layers of two or more, the metals used in the layers may be different or the same.
[0106] The thickness of the metal thin film layer is preferably in the range of 10 to 200 nm. If it is thinner than 10 nm, there is a risk that the transfer film of the present invention cannot be given the desired metallic luster, etc., so it is not preferred. If it is thicker than 200 nm, there is a risk that the plastic film will be deformed or modified due to the heat when the metal thin film layer is formed and the heat during the transfer process, and there is a risk that the transfer film of the present invention cannot be given the desired metallic luster, etc., so it is not preferred.
[0107] The method for forming the metal thin film layer may be a conventionally known method for forming a metal thin film layer, such as vacuum deposition, sputtering, or chemical vapor deposition (CVD), and may be appropriately selected according to the purpose.
[0108] Furthermore, when the transfer film of the present invention forms a decorative layer, the types of the metal thin film layer, the coloring layer, the printing layer, and the metal base layer to be formed, and the order of formation can be appropriately selected according to the purpose. In addition, the metal thin film layer, the coloring layer, the printing layer, the metal base layer, and the adhesive layer described later can be formed on the entire surface of the protective layer or only on a portion thereof, and the position of formation can be appropriately selected according to the purpose.
[0109] (Adhesive layer)
[0110] The adhesive layer formed on the transfer film of the present invention can be any thermoplastic resin generally used for transfer films, and there is no particular restriction on this. It can use existing known resins such as acrylic resins, polyethylene resins, polypropylene resins, polystyrene resins, vinyl chloride resins, polyester resins, carbamate resins, and vinyl acetate resins. It can be any one of them, or a mixed resin of two or more, or a copolymer resin of two or more thereof, and it can be appropriately selected according to the transferred object used. In addition, if a resin with good compatibility with the resin used in the transferred object is used, the compatibility with the transferred object is also good, so it is preferred.
[0111] The thickness of the adhesive layer may be appropriately selected within a range that can achieve the above-mentioned purpose, and is preferably in the range of 0.5 to 10 μm.
[0112] The adhesive layer may be formed by any conventionally known coating method such as gravure coating, reverse coating, die coating, reverse gravure coating, or bar coating, and may be appropriately selected depending on the intended purpose.
[0113] The laminate of the present invention can be obtained by sequentially forming the above-mentioned layers on a substrate as a transfer target.
[0114] Furthermore, in order to obtain the laminate of the present invention, a method of forming each layer on a substrate using the transfer film of the present invention is most preferred.
[0115] (Base material)
[0116] The substrate can be made of known materials such as acrylic resin, polyethylene resin, polypropylene resin, polystyrene resin, vinyl chloride resin, polyester resin, urethane resin, vinyl acetate resin, ABS resin, polycarbonate resin, etc. according to the desired purpose, and can be any one of them, or a mixed resin of two or more thereof, or a copolymer resin of two or more thereof. In addition, these substrates can be transparent or colored.
[0117] Example
[0118] The present invention will be described in more detail below with reference to Examples and Comparative Examples, but the present invention is not limited to the Examples.
[0119] [Examples 1 to 11, Comparative Examples 1 to 8]
[0120] [Production of transfer film]
[0121] The following steps 1 to 4 are performed in order to obtain a transfer film in which a release layer, a protective layer, an intermediate layer, and an adhesive layer are sequentially formed on a polyethylene terephthalate film.
[0122] (Step 1) A thermosetting acrylic melamine resin was applied on a polyethylene terephthalate film having a thickness of 25 μm by a bar coating method to form a release layer having a thickness of 0.5 μm.
[0123] (Step 2) A thermoplastic acrylic resin was applied on the release layer by a bar coating method to form a protective layer having a thickness of 1 μm.
[0124] (Step 3) An acrylic polyol resin and an HDI-based polyisocyanate compound are mixed and applied onto the protective layer by a bar coating method to form an intermediate layer.
[0125] Table 1 shows the hydroxyl value of the acrylic polyol, the ratio of the total number of isocyanate groups contained in the polyisocyanate compound to the total number of hydroxyl groups contained in the polyol compound ([NCO] / [OH] ratio), and the thickness of the intermediate layer.
[0126] (Step 4) A copolymer resin of an acrylic resin and a vinyl acetate resin is applied on the intermediate layer by a bar coating method to form an adhesive layer having a thickness of 2 μm.
[0127] [Production of Laminated Body]
[0128] The above steps are carried out, and the obtained transfer film is placed on an ABS substrate in a manner such that the adhesive layer becomes the substrate side. Pressurization and heating are performed from the plastic film side using a roller transfer machine. After transfer processing is performed at a transfer temperature of 200°C and a transfer speed of 50 mm / sec, the plastic film including the release layer is quickly peeled off to obtain a laminate.
[0129] [Example 12]
[0130] [Production of transfer film]
[0131] The following steps 1 to 6 are performed in order to obtain a transfer film in which a release layer, a protective layer, an intermediate layer, a metal base layer, a metal thin film layer and an adhesive layer are sequentially formed on a polyethylene terephthalate film.
[0132] (Step 1) A thermosetting acrylic melamine resin was applied onto a polyethylene terephthalate film having a thickness of 25 μm by a bar coating method to form a release layer having a thickness of 0.5 μm.
[0133] (Step 2) A thermoplastic acrylic resin was applied on the release layer by a bar coating method to form a protective layer having a thickness of 1 μm.
[0134] (Step 3) An acrylic polyol resin having a hydroxyl value of 24 mgKOH / g and an HDI-based polyisocyanate compound are mixed in such a manner that the ratio of the total number of isocyanate groups contained in the polyisocyanate compound to the total number of hydroxyl groups contained in the polyol compound ([NCO] / [OH] ratio) reaches 0.8, and the mixture is applied onto the protective layer by a rod coating method to form an intermediate layer having a thickness of 2 μm.
[0135] (Step 4) An acrylic polyol resin having a hydroxyl value of 24 mgKOH / g and an HDI-based polyisocyanate compound are mixed in such a manner that the ratio of the total number of isocyanate groups contained in the polyisocyanate compound to the total number of hydroxyl groups contained in the polyol compound ([NCO] / [OH] ratio) reaches 2.0, and the mixture is applied onto the intermediate layer by a rod coating method to form a metal base layer having a thickness of 1 μm.
[0136] (Step 5) Chromium is formed on the metal base layer by vacuum deposition to form a chromium thin film layer with a thickness of 50 nm.
[0137] (Step 6) A copolymer resin of an acrylic resin and a vinyl acetate resin is applied on the chromium thin film layer by a bar coating method to form an adhesive layer having a thickness of 2 μm.
[0138] [Production of Laminated Body]
[0139] The above steps were carried out, and a laminate was obtained in the same manner as in Example 1 using the obtained transfer film.
[0140] [Example 13]
[0141] [Production of transfer film]
[0142] The following steps 1 to 4 are performed in order to obtain a transfer film in which a release layer, a protective layer, an intermediate layer, and an adhesive layer are sequentially formed on a polyethylene terephthalate film.
[0143] (Step 1) A thermosetting acrylic melamine resin was applied onto a polyethylene terephthalate film having a thickness of 25 μm by a bar coating method to form a release layer having a thickness of 0.5 μm.
[0144] (Step 2) A thermoplastic acrylic resin was applied on the release layer by a bar coating method to form a protective layer having a thickness of 1 μm.
[0145] (Step 3) An acrylic polyol resin having a hydroxyl value of 24 mgKOH / g and an HDI-based polyisocyanate compound are mixed in such a manner that the ratio of the total number of isocyanate groups contained in the polyisocyanate compound to the total number of hydroxyl groups contained in the polyol compound ([NCO] / [OH] ratio) reaches 0.8, and the mixture is applied onto the protective layer by a rod coating method to form an intermediate layer having a thickness of 3 μm.
[0146] (Step 4) A copolymer resin of an acrylic resin and a vinyl acetate resin is applied on the intermediate layer by a bar coating method to form an adhesive layer having a thickness of 2 μm.
[0147] [Production of Laminated Body]
[0148] The above steps were carried out, and a laminate was obtained in the same manner as in Example 1 using the obtained transfer film.
[0149] [Example 14]
[0150] [Production of transfer film]
[0151] The following steps 1 to 4 are performed in order to obtain a transfer film in which a release layer, a protective layer, a coloring layer, and an adhesive layer are sequentially formed on a polyethylene terephthalate film.
[0152] (Step 1) A thermosetting acrylic melamine resin was applied onto a polyethylene terephthalate film having a thickness of 25 μm by a bar coating method to form a release layer having a thickness of 0.5 μm.
[0153] (Step 2) A thermoplastic acrylic resin was applied on the release layer by a bar coating method to form a protective layer having a thickness of 1 μm.
[0154] (Step 3) An acrylic polyol resin having a hydroxyl value of 24 mgKOH / g and an HDI-based polyisocyanate compound are mixed in such a manner that the ratio of the total number of isocyanate groups contained in the polyisocyanate compound to the total number of hydroxyl groups contained in the polyol compound ([NCO] / [OH] ratio) is 0.8, and a black pigment is further added in an amount of 10% by weight relative to the resin, and the resultant is applied onto the protective layer by a rod coating method to form a colored layer having a thickness of 3 μm.
[0155] (Step 4) On the colored layer, a copolymer resin of an acrylic resin and a vinyl acetate resin is applied by a bar coating method to form an adhesive layer having a thickness of 2 μm.
[0156] [Production of Laminated Body]
[0157] The above steps were carried out, and a laminate was obtained in the same manner as in Example 1 using the obtained transfer film.
[0158] [Example 15]
[0159] [Production of transfer film]
[0160] The following steps 1 to 5 are performed in order to obtain a transfer film in which a release layer, a protective layer, a metal base layer, a metal thin film layer and an adhesive layer are sequentially formed on a polyethylene terephthalate film.
[0161] (Step 1) A thermosetting acrylic melamine resin was applied onto a polyethylene terephthalate film having a thickness of 25 μm by a bar coating method to form a release layer having a thickness of 0.5 μm.
[0162] (Step 2) A thermoplastic acrylic resin was applied on the release layer by a bar coating method to form a protective layer having a thickness of 1 μm.
[0163] (Step 3) An acrylic polyol resin having a hydroxyl value of 24 mgKOH / g and an HDI-based polyisocyanate compound are mixed in such a manner that the ratio of the total number of isocyanate groups contained in the polyisocyanate compound to the total number of hydroxyl groups contained in the polyol compound ([NCO] / [OH] ratio) reaches 2.0, and the mixture is applied onto the protective layer by a rod coating method to form a metal base layer having a thickness of 3 μm.
[0164] (Step 4) Chromium is formed on the metal base layer by vacuum deposition to form a chromium thin film layer with a thickness of 50 nm.
[0165] (Step 5) A copolymer resin of an acrylic resin and a vinyl acetate resin is applied on the chromium thin film layer by a bar coating method to form an adhesive layer having a thickness of 2 μm.
[0166] [Production of Laminated Body]
[0167] The above steps were carried out, and a laminate was obtained in the same manner as in Example 1 using the obtained transfer film.
[0168] [Example 16]
[0169] [Production of transfer film]
[0170] The following steps 1 to 6 are performed in order to obtain a transfer film in which a release layer, a protective layer, a coloring layer, a metal base layer, a metal thin film layer and an adhesive layer are sequentially formed on a polyethylene terephthalate film.
[0171] (Step 1) A thermosetting acrylic melamine resin was applied onto a polyethylene terephthalate film having a thickness of 25 μm by a bar coating method to form a release layer having a thickness of 0.5 μm.
[0172] (Step 2) An acrylic polyol resin having a hydroxyl value of 24 mgKOH / g and an HDI-based polyisocyanate compound are mixed in such a manner that the ratio of the total number of isocyanate groups contained in the polyisocyanate compound to the total number of hydroxyl groups contained in the polyol compound ([NCO] / [OH] ratio) reaches 0.8, and the mixture is applied onto the release layer by a rod coating method to form a protective layer having a thickness of 1 μm.
[0173] (Step 3) An acrylic polyol resin having a hydroxyl value of 24 mgKOH / g and an HDI-based polyisocyanate compound are mixed in such a manner that the ratio of the total number of isocyanate groups contained in the polyisocyanate compound to the total number of hydroxyl groups contained in the polyol compound ([NCO] / [OH] ratio) is 0.8, and a black pigment is further added in an amount of 10% by weight relative to the resin. The resultant is applied onto the protective layer by a rod coating method to form a colored layer having a thickness of 1 μm.
[0174] (Step 4) An acrylic polyol resin having a hydroxyl value of 24 mgKOH / g and an HDI-based polyisocyanate compound are mixed in such a manner that the ratio of the total number of isocyanate groups contained in the polyisocyanate compound to the total number of hydroxyl groups contained in the polyol compound ([NCO] / [OH] ratio) reaches 2.0, and the mixture is applied onto the colored layer by a rod coating method to form a metal base layer having a thickness of 1 μm.
[0175] (Step 5) Chromium is formed on the metal base layer by vacuum deposition to form a chromium thin film layer with a thickness of 50 nm.
[0176] (Step 6) A copolymer resin of an acrylic resin and a vinyl acetate resin is applied on the chromium thin film layer by a bar coating method to form an adhesive layer having a thickness of 2 μm.
[0177] [Production of Laminated Body]
[0178] The above steps were carried out, and a laminate was obtained in the same manner as in Example 1 using the obtained transfer film.
[0179] [Comparative Example 7]
[0180] [Production of transfer film]
[0181] The following steps 1 to 5 are performed in order to obtain a transfer film in which a release layer, a protective layer, a metal base layer, a metal thin film layer and an adhesive layer are sequentially formed on a polyethylene terephthalate film.
[0182] (Step 1) A thermosetting acrylic melamine resin was applied onto a polyethylene terephthalate film having a thickness of 25 μm by a bar coating method to form a release layer having a thickness of 0.5 μm.
[0183] (Step 2) An acrylic polyol resin having a hydroxyl value of 24 mgKOH / g and an HDI-based polyisocyanate compound are mixed in such a manner that the ratio of the total number of isocyanate groups contained in the polyisocyanate compound to the total number of hydroxyl groups contained in the polyol compound ([NCO] / [OH] ratio) reaches 0.8, and the mixture is applied onto the release layer by a rod coating method to form a protective layer having a thickness of 1 μm.
[0184] (Step 3) An acrylic polyol resin having a hydroxyl value of 24 mgKOH / g and an HDI-based polyisocyanate compound are mixed in such a manner that the ratio of the total number of isocyanate groups contained in the polyisocyanate compound to the total number of hydroxyl groups contained in the polyol compound ([NCO] / [OH] ratio) reaches 2.0, and the mixture is applied onto the protective layer by a rod coating method to form a metal base layer having a thickness of 1 μm.
[0185] (Step 4) Chromium is formed on the metal base layer by vacuum deposition to form a chromium thin film layer with a thickness of 50 nm.
[0186] (Step 5) A copolymer resin of an acrylic resin and a vinyl acetate resin is applied on the metal thin film layer by a bar coating method to form an adhesive layer having a thickness of 2 μm.
[0187] [Production of Laminated Body]
[0188] The above steps were carried out, and a laminate was obtained in the same manner as in Example 1 using the obtained transfer film.
[0189] [Examples 17 to 20]
[0190] [Production of transfer film and laminate]
[0191] A laminated body was obtained in the same manner as in Example 1 except that the polyol compound and the polyisocyanate compound in step 3 of Example 1 were combined as shown in Table 3.
[0192] [Examples 21 to 29, Comparative Examples 8 to 14]
[0193] [Production of transfer film]
[0194] The functional layers (protective layer, intermediate layer, coloring layer, metal base layer, metal thin film layer) of the present invention are combined and stacked in the manner shown in Table 3 to prepare a transfer film. It should be noted that the stacking order is the order of plastic film / release layer / protective layer / intermediate layer / coloring layer / metal base layer / metal thin film layer / adhesive layer. That is, the layers constituting the functional layers of the present invention shown in Table 4 are formed in the order from the left side of the table. The formation method of each layer is in accordance with Examples 1 to 16 to prepare a transfer film. At this time, the hydroxyl value of the acrylic polyol, the ratio of the total number of isocyanate groups contained in the polyisocyanate compound to the total number of hydroxyl groups contained in the polyol compound ([NCO] / [OH] ratio), and the thickness of each layer are shown in Table 3. However, a layer with a thickness of 0 μm indicates that the layer is not formed. The protective layers of Examples 21 to 25, Comparative Examples 8 to 12, and Comparative Example 14 use the same thermoplastic acrylic resin as Step 2 (protective layer) of Example 1. In Comparative Example 9, a thermoplastic acrylic resin was used as an intermediate layer to form an intermediate layer with a thickness of 1 μm by a bar coating method. Furthermore, as a coloring layer, a black pigment was added to a thermoplastic acrylic resin in an amount of 10% by weight relative to the resin, and a coloring layer with a thickness of 6 μm was formed by a bar coating method. Al, Cr, and In in the table represent aluminum, chromium, and indium, respectively, and the metal thin film layers were all formed by vacuum evaporation to a thickness of 50 nm.
[0195] [Production of Laminated Body]
[0196] A laminate was obtained in the same manner as in Example 1 using the transfer film obtained as described above.
[0197] [Evaluation of Each Transfer Film and Laminated Body]
[0198] The transfer films obtained in Examples 1 to 29 and Comparative Examples 1 to 14 and the laminates obtained therefrom were subjected to the following chemical resistance evaluation and foil burr property evaluation. The results are shown in Tables 1 to 3.
[0199] [Chemical resistance test (sunscreen cosmetics)]
[0200] On the surface of the laminate obtained above (protective layer), 0.15 g of commercially available sunscreen cosmetics was evenly applied to a portion of 50 mm in length and 50 mm in width. The laminate was placed in a constant temperature bath at 55°C for 24 hours. The laminate was taken out, and after the sunscreen cosmetics were washed off with a cleaning solution, the state of the portion (test surface) coated with the sunscreen cosmetics was visually observed and evaluated according to the following criteria. The sunscreen cosmetic used was a commercially available SPF50 sunscreen cosmetic.
[0201] ◎: No expansion, cracking, discoloration or other changes in appearance.
[0202] ○: There are slight changes in appearance such as expansion, cracking, and discoloration, but it has no effect on actual use.
[0203] △: There are changes in appearance such as swelling, cracking, and discoloration.
[0204] ×: There are significant changes in appearance such as swelling, cracking, and discoloration.
[0205] [Chemical resistance test (gasoline)]
[0206] The chemical resistance test was carried out under the following three conditions. The gasoline used was the standard gasoline for automobiles specified in JIS-K-2202.
[0207] (1) 0.1 ml of gasoline was dropped onto the surface (protective layer side) of the laminate at 25° C., and 5 minutes after the gasoline evaporated, the appearance of the portion (test surface) where gasoline was dropped was evaluated.
[0208] (2) After the test of (1), the sample was further left in a constant temperature chamber at 80°C. After 10 minutes, the appearance of the portion (test surface) to which gasoline had been dropped was evaluated.
[0209] (3) After immersion at 25°C for 30 minutes, the appearance of the test surface was evaluated.
[0210] ◎: No changes in appearance such as expansion, cracking, or discoloration were observed in any of the tests (1) to (3).
[0211] ○: In any of the tests (1) to (3), slight changes in appearance such as swelling, cracking, and discoloration were observed, but the actual use was not affected.
[0212] Δ: In any of the tests (1) to (3), there were changes in appearance such as swelling, cracking, and discoloration.
[0213] ×: In any of the tests (1) to (3), there was a significant change in appearance such as swelling, cracking, or discoloration.
[0214] [Evaluation of foil burr properties]
[0215] When a laminated body was produced using the transfer film, the presence or absence of foil burrs was evaluated.
[0216] ◎: No foil burrs were generated.
[0217] ○: Slight foil burrs were generated, but did not affect practical use.
[0218] ×: Foil burrs were generated.
[0219] [Table 1]
[0220]
[0221] [Table 2]
[0222]
[0223] [Table 3]
[0224]
[0225] [Table 4]
[0226]
[0227] As described above, according to the transfer film of the present invention, it is possible to obtain a laminated body with less occurrence of foil burrs and excellent chemical resistance.
[0228] Description of Reference Numerals
[0229] 1 plastic wrap
[0230] 2 Release layer
[0231] 3 protective layers
[0232] 4 Middle Layer
[0233] 5Metal base layer
[0234] 6Metal film layer
[0235] 7 Adhesive layer
[0236] 8. Substrate
[0237] 10 transfer layer
[0238] 11 Transfer film
[0239] 12-layer stack
Claims
1. A transfer film, wherein at least a functional layer and an adhesive layer are sequentially formed on a plastic film, wherein the transfer film is characterized in that: At least the thickness of the functional layer satisfying the following conditions a, b, and c is 3 μm or more and 8 μm or less, and The functional layer comprises at least a protective layer and an intermediate layer, and, The thickness of the protective layer satisfying the following conditions a, b and c is 0.5 μm or more and 5 μm or less, and The thickness of the intermediate layer satisfying the following conditions a, b and c is 0.5 μm or more and 5 μm or less, a: contains at least an acrylic polyol compound and a polyisocyanate compound, b: The hydroxyl value of the acrylic polyol compound is 20 mgKOH / g or more and 60 mgKOH / g or less, c: The ratio of the total number of isocyanate groups contained in the polyisocyanate compound to the total number of hydroxyl groups contained in the acrylic polyol compound, that is, the [NCO] / [OH] ratio is 0.5 or more and 3.0 or less.
2. A transfer film, wherein at least a functional layer and an adhesive layer are sequentially formed on a plastic film, wherein the transfer film is characterized in that: At least the thickness of the functional layer satisfying the following conditions a, b, and c is 3 μm or more and 8 μm or less, and The functional layer comprises a protective layer, an intermediate layer, a metal base layer and a metal film layer, and, The thickness of the protective layer satisfying the following conditions a, b and c is 0.5 μm or more and 5 μm or less, and The thickness of the intermediate layer satisfying the following conditions a, b and c is 0.5 μm or more and 5 μm or less, and The thickness of the metal base layer satisfying the following conditions a, b and c is 0.5 μm or more and 2 μm or less, a: contains at least an acrylic polyol compound and a polyisocyanate compound, b: The hydroxyl value of the acrylic polyol compound is 20 mgKOH / g or more and 60 mgKOH / g or less, c: The ratio of the total number of isocyanate groups contained in the polyisocyanate compound to the total number of hydroxyl groups contained in the acrylic polyol compound, that is, the [NCO] / [OH] ratio is 0.5 or more and 3.0 or less.
3. The transfer film according to claim 1, wherein The functional layer at least includes a protective layer, an intermediate layer and a decorative layer.
4. The transfer film according to claim 3, wherein The decorative layer includes at least one of a metal base layer, a metal thin film layer, a colored layer and a printed layer.
5. The transfer film according to claim 4, wherein The decorative layer comprises a metal base layer and a metal film layer.
6. A laminated body, characterized in that: The invention is obtained by transferring the transfer film according to any one of claims 1 to 5 onto a substrate.
7. A laminated body, characterized in that: At least an adhesive layer and a functional layer are sequentially formed on a substrate. In the laminate, at least the thickness of the functional layer satisfying the following conditions a, b, and c is 3 μm or more and 8 μm or less, and The functional layer comprises at least a protective layer and an intermediate layer, and, The thickness of the protective layer satisfying the following conditions a, b and c is 0.5 μm or more and 5 μm or less, and The thickness of the intermediate layer satisfying the following conditions a, b and c is 0.5 μm or more and 5 μm or less, a: contains at least an acrylic polyol compound and a polyisocyanate compound, b: The hydroxyl value of the acrylic polyol compound is 20 mgKOH / g or more and 60 mgKOH / g or less, c: The ratio of the total number of isocyanate groups contained in the polyisocyanate compound to the total number of hydroxyl groups contained in the acrylic polyol compound, that is, the [NCO] / [OH] ratio is 0.5 or more and 3.0 or less.
8. A laminated body, characterized in that: At least an adhesive layer and a functional layer are sequentially formed on a substrate. In the laminate, at least the thickness of the functional layer satisfying the following conditions a, b, and c is 3 μm or more and 8 μm or less, and The functional layer comprises a protective layer, an intermediate layer, a metal base layer and a metal film layer, and, The thickness of the protective layer satisfying the following conditions a, b and c is 0.5 μm or more and 5 μm or less, and The thickness of the intermediate layer satisfying the following conditions a, b and c is 0.5 μm or more and 5 μm or less, and The thickness of the metal base layer satisfying the following conditions a, b and c is 0.5 μm or more and 2 μm or less, a: contains at least an acrylic polyol compound and a polyisocyanate compound, b: The hydroxyl value of the acrylic polyol compound is 20 mgKOH / g or more and 60 mgKOH / g or less, c: The ratio of the total number of isocyanate groups contained in the polyisocyanate compound to the total number of hydroxyl groups contained in the acrylic polyol compound, that is, the [NCO] / [OH] ratio is 0.5 or more and 3.0 or less.
9. The laminate according to claim 7, wherein: The functional layer at least includes a protective layer, an intermediate layer and a decorative layer.
10. The laminate according to claim 9, wherein The decorative layer includes at least one of a metal base layer, a metal thin film layer, a colored layer and a printed layer.
11. The laminate according to claim 10, wherein The decorative layer comprises a metal base layer and a metal film layer.
Citation Information
Patent Citations
Transfer sheet
JP2003154794A
Transfer printing laminated body
CN102529257A
Thermal transfer film and method for manufacturing same
CN103419523A